Primary Education: Assessing and Planning Learning - Craft, Anna (Routledge, 1996)
This wide ranging sourcebook draws together a range of recent and specially commissioned pieces which examine how policy development and research findings have influenced planning and assessing learning for young children. Topics covered include standards, quality control, league tables, teacher and performance assessment. It also looks at the enabling of learning, focusing on authentic activity and learning, implicit values, the role of learner choice and classroom management. The book also raises which will effect assessing and planning learning into the next century, and sets an agenda for reform and development including teacher training, funding of primary education, early years education and entitlement in primary school.